Changes in the Fracture Toughness under Mode II Loading of Low Calcium Fly Ash (LCFA) Concrete Depending on Ages - Golewski, Grzegorz Ludwik (Materials (Basel), 2020)
This study investigated the influence of the curing time on the fracture toughness of concrete produced with different content of low calcium fly ash (LCFA). During the study, the amounts of 20% and 30% of pozzolanic additive were used. In order to observe the effect of the applied pozzolanic additive on the analyzed concrete properties, the obtained results were compared with the values obtained for the reference concrete. Compressive strength—f(cm) and fracture toughness, by using mode II loading—K(IIc) (shearing), were determined between the 3rd and 365th days of curing. In the course of experiments, changes in the development of cracks in individual series of concrete were also analyzed. In addition, the microstructures of all composites and the nature of macroscopic crack propagation in mature concretes were assessed. It was observed that the greatest increase in fracture toughness at shear was in the case of reference concrete during the first 28 days, whereas, in the case of concretes containing LCFA, in the period of time above 4 weeks. Furthermore, concrete without the LCFA additives were characterized by a brittle fracture. In contrast to it, concretes with LCFA additives are mainly characterized by a quasi-plastic process of failure. Moreover, most of the samples showed a typical pattern of the destruction that occurs as a result of shearing. The presented test results may be helpful in selecting the composition of concrete mixtures containing LCFA to be used in concrete and reinforced concrete structures subjected to shear loads.